Errors and Expectations: Addressing the Challenges of Graduate Writing in Tribhuvan University, Nepal - Pandey, Hem Lal (JODEM: Journal of Language and Literature, 2024)
As teachers working with students for whom English is a second language, we consistently face numerous challenges related to language use in academic writing, particularly among graduate students in the Humanities and Social Sciences at Tribhuvan University (TU). A shared struggle of students is evident in meeting basic language requirements of the graduate writing due to their limited writing experience and inadequate exposure to the theoretical foundations of the language of academic writing. Drawing from my own experience of assisting students in their writing, supervising them in their thesis writing, and teaching writing courses over a decade, in this paper, I aim to identify and address some of the most common and recurring language issues that students encounter. The theoretical concepts of error explored in this paper are grounded in the discipline of composition studies, shaped by the contributions of eminent scholars and their works such as Mina P. Shaughnessy’s Errors and Expectations, David Bartholomae’s “The Study of Error,” and Joseph M. Williams’ “The Phenomenology of Error.” In this paper, I employ an autoethnographic account as a methodology for identifying major concerns of ‘errors’ and providing accompanying examples. While no predetermined rules can govern academic language, this paper selects some of the important characteristic features of academic language in the form of a guideline. Through the proposed guidelines, if taken into consideration, student writers will be able to empower themselves in navigating the concept of ‘errors’ and addressing the ‘expectations’ of academic writing conventions in the university settings. Exploring this topic in the context of graduate writing at TU, this paper argues that the challenges of graduate writers in their writing process can be mitigated through consorted effort of the instructors with the tool of a working guideline as discussed in the paper.